Basic Principles and Uniform Terminology for the Head-Neck Junction in Hip Replacement. Issue 2 (March 2015) - Werner, Paul H.; Ettema, Harmen B.; Witt, Florian; Morlock, Michael M.; Verheyen, Cees C.P.M.
Recent problems with large head metal on metal hip replacements have spiked renewed interest in the head-neck junction. A thorough knowledge of the principles of the locking mechanism, the assembly technique and affecting factors on the strength of this junction is needed. Currently a confusing variability in terms is used to describe this junction. This overcomplicates an already complex issue. The purpose of this literature review is to collect and list the different terms used and to propose a uniform terminology. Two authors independently searched the electronic databases of PubMed, CINAHL and MEDLINE with specific key words and combinations according to the PRISMA guidelines. The initial search yielded a total of 518 articles with ultimately 53 articles included in the present analysis. No consensus for a uniform term for the 2 sides of the head-stem junction was found. Since there is already pronounced variability in taper designs between different manufacturers (even so similarly named, e.g. "12/14"), a uniform terminology could be the first step to simplify the situation. "Male" and "female taper" is proposed as the appropriate terminology for the stem and head junction in hip replacement, respectively. The importance of the assembly technique understanding the principles of the locking mechanism is emphasised.